Technical Performance Evaluation Of Flood Control Projects In Urban Rivers And Corrective Solutions-Case Study: Rivers Talar In Mazandaran - Mihammad Moradi; Mohammd aamel Sadeghi; Abdolrasul Telvari (مهندسی و مدیریت ساخت, 2017)
Flood control structures due to the damaging effects of flooding, which have caused many damage to agricultural marginal land and peripheral facilities for many years. . . Imported, designed and constructed. Due to floods, the height of water in the river rises and causes it to flow out of the main river. Plain floods and rivers adjacent to the rivers, which, due to their particular circumstances, are suitable spaces for carrying out economic and social activities, are always exposed to the dangers of the occurrence of Sala. Thus, in these areas, the implementation of design plans is used to prevent the destructive effects of flooding. In the Ghomeshahr River Hall and in the area of ​​Ghaemshahr, plans have been implemented as a river regeneration plan. In this research, technical and hydraulic performance of these projects will be investigated and corrective solutions should be presented in the event of problems arising from the organization.